Conservation of the largest cervid of South America : interactions between people and the Vulnerable marsh deer Blastocerus dichotomus - Iezzi, María Eugenia; Fracassi, Natalia; Pereira, Javier Adolfo (Cambridge University Press, 2017)
Wild ungulates, and particularly deer, can cause severe damage to commercial plantations, resulting in reduced tolerance of their presence by forestry producers. The marsh deer Blastocerus dichotomus, categorized as Vulnerable on the IUCN Red List, is declining throughout South America. A population of c. 500 individuals survive within a matrix of commercial plantations in the lower delta of the Paraná River, the southernmost stronghold for the species. Local forestry producers usually report that damage to plantations is attributable to marsh deer, thus justifying persecution of the species. Seventy-six forestry producers (representing c. 33% of the total plantation area of the lower delta) were interviewed using a semi-structured questionnaire to assess perceived levels of tree damage, associated economic losses, and attitudes towards the deer. Simultaneously, plantation stands were surveyed to quantify the actual tree damage caused by this ungulate. Seventy-six percent of producers reported damage to trees by deer (i.e. browsing, fraying caused by antler rubbing) but most of them perceived low levels of damage per property (median < 0.2%), with negligible economic effects. However, 5% of producers (all of them with ≤ 2 km2 in production, usually family enterprises) perceived high levels of damage and economic losses, and supported deer hunting as a management option. Field surveys indicated that damage caused by deer could be more severe than perceived by producers, although spatially confined within the landscape. Monitoring of damage perception by forestry producers, and compensation schemes to assist small producers are necessary for adequate management of this threatened marsh deer population.